Disability prevention, detection and assistance in primary health care services in the state of São Paulo, Brazil - Zarili, Thais Fernanda Tortorelli [UNESP]; Castanheira, Elen Rose Lodeiro [UNESP]; Nunes, Luceime Olivia [UNESP]; Mendonça, Carolina Siqueira [UNESP]; Couto, Caroline Eliane; Rossato, Sinara Laurini; Nemes, Maria Ines Baptistella (FapUNIFESP (SciELO), 2024)
The objective of this study was to assess the performance of primary health care (PHC) services for disability prevention, detection and assistance in the state of São Paulo. The study included 2739 health services, from 514 munic-ipalities. 128 organizational quality indicators of the QualiAB instrument referring to the evalua-tive dimension “Attention to disability in primary health care services”. The association of health care performance score of each domain with inde-pendent variables, health assessment, and support network were tested using of multiple linear re-gression. The performance percentage was 61.6% for all domains, 73.6% for structure (inputs and human resources), 68.7% for qualification of pre-natal care, 56.1% for qualification of child health care, 55.8% for prevention of disabilities related to chronic conditions, and 53.9% for attention to people with disabilities and caregivers. There was a significant association with variables related to the type of service and participation in service evaluations. PHC services still perform incipient actions for the prevention, surveillance and diagnosis of disabilities as well as for comprehensive care for people with disabilities.
Prevenção, detecção e assistência à deficiência em serviços de atenção primária à saúde do Estado de São Paulo, Brasil
Keywords: Health assessment; Health services; People with disabilities; Primary health care